South Asian and Chinese International Students in Canada: The Role of Social Connections in their Settlement and Integration - Mandell, Nancy; Phonepraseuth, Janice; Borras, Jana; Lam, Larry (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2022)
Based on 18 interviews with South Asian and Chinese international students in Canadian universities, we examine the academic, financial, and social settlement and integration obstacles they encounter, and strategies implemented. Key to promoting academic and sociocultural integration are the formal and informal social connections students establish on and off campus. Online information and sociocultural, financial, and emotional guidance from other students, family, friends, faith, and ethno-racial and community groups promote students’ settlement and integration (Chira, 2013; El Masri & Khan, 2022; Kang, 2020; Wessendorf & Phillimore, 2019). Our work contributes to migration and higher education studies by highlighting the crucial role of social connections as the “connective tissue” between Canada’s settlement goals and public integration outcomes (Ager & Strang, 2008, p. 177). Continued growth of international students in universities necessitates a more carefully executed and expansive role for universities in facilitating their settlement and integration.